Enhancing Event Continuity Through Digital Marketing, Experience, and Consumer Loyalty: Insights from MotoGP Mandalika - Zefanya Andryan Girsang; Sri Maryanti; Tifani Dame Hasany; Dhanny Safitri; Hibatullah Falih Musyaffa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Large-scale international sporting events increasingly depend on effective digital engagement and memorable experiences to ensure long-term continuity. This study examines the effects of digital marketing and event experience on consumer loyalty and investigates how loyalty subsequently influences event continuity in the context of the MotoGP Mandalika, Indonesia. It also assesses the moderating role of perceived event quality. A quantitative research design was employed, with data collected from 248 MotoGP Mandalika spectators using a structured questionnaire. The proposed model was analyzed using Structural Equation Modeling with the Partial Least Squares approach (SEM-PLS) to test direct, indirect, and moderating effects. The results indicate that digital marketing and event experience significantly and positively influence consumer loyalty. Consumer loyalty, in turn, has a strong effect on event continuity, highlighting its crucial role in sustaining large-scale sporting events. However, perceived event quality does not moderate the relationships between digital marketing or event experience and consumer loyalty, suggesting that loyalty is shaped primarily by direct digital engagement and on-site experiential factors rather than by overall quality perceptions. The predominance of domestic respondents limits the generalizability of the findings to international audiences. This study contributes to the event and sports tourism literature by positioning consumer loyalty as a central mechanism linking marketing efforts and event experiences to long-term event continuity. It further clarifies the limited moderating role of perceived event quality, offering new insights into loyalty formation in large-scale international sporting events, particularly within emerging tourism destinations